(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2015)
United Nations persevered since its inception on the protection of human rights by taking various means and granting broad powers to the Security Council in order to facilitate its tasks in the maintenance of international peace and security, and the most important endeavors the establishment of the International Criminal Court, which was preceded by some applications and attempts that did not come out on its own character and temporary. This paper was devoted to the study of history of the United Nations in the establishment of criminal tribunals for the fight against impunity and what came along with it from advantages and disadvantages, taking into account the fact that the Security Council had a role in the establishment of these courts, which did not come out of the United Nations Department one way or another. Key-words: UN - International criminal courts - against impunity.